The Kolubung Tradition in West Pangian Village In George Herbert Mead's Theory of Symbolic Interactionism - Matulandi Arthur Tewu; Jeysi Preasilia Paendong; Nontje Mery Timbuleng; Olga Neltje Komaling; Ventje Albert Talumepa (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
This research aims to understand how the meaning of this tradition is formed through social interactions, using the symbolic interactionism approach of George Herbert Mead. The main question posed is how individuals and the community of Pangian Barat Village develop shared meaning through participation in the Kolubung tradition. The research methodology employs a qualitative approach with in-depth interviews, participatory observation, and documentation, along with thematic analysis. Data were collected from members of the community involved in the Kolubung tradition and analyzed to identify the social meanings that are formed in the practice. The results of the study indicate that the Kolubung Tradition functions as a symbol of mourning and as a space for building social solidarity and strengthening relationships among community members. This finding highlights the importance of preserving local traditions as part of social identity and community solidarity, even in the face of changing challenges. This research enriches the understanding of the role of symbols in local traditions and can serve as a foundation for further research regarding the role of the younger generation in maintaining these traditions.